Uso de citometria de fluxo para análise de óxido nítrico intracelular em monócidos e neutrófilos do sangue periférico de pacientes com nefropatia crônica do enxerto - Natalia Castro de Carvalho Schachnik (2008)
Nitric oxide (NO) is one of the most important biosynthesized molecules and participates as a mediator in various biological processes. The laboratorial determination of NO represents a challenge principally because of its unreliable half-life and concentration in biological samples. Recently, flow cytometry was proposed as a method for the determination of intracellular NO with 4,5-diaminofluorescein diacetate (DAF-2DA). Increasing evidence suggests a role for the NO resulting from inducible NO synthase (iNOS) as a mediator in the graft rejection process. Renal transplant is the treatment of choice for patients that are in the final stage of kidney disease and the chronic nephropathy of the graft is the most important cause of loss of a transplanted kidney. In the present study, the protocol for the determination of intracellular NO in monocytes and circulating neutrophils by flow cytometry was optimized, and the profile for the production of this compound in kidney-transplanted individuals with chronic nephropathy of the graft (n=11) and healthy individuals (n=10) was determined. No difference in the production of NO was observed in the two groups. The production of NO in monocytes and circulating neutrophils in patients with chronic nephropathy of the graft is probably suppressed as a result of the action of immunosuppressors.